2021
DOI: 10.3844/ajavsp.2021.212.216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Listeria monocytogenes in Raw Cow's Milk in the Region of Batna, Algeria

Abstract: The aim of this study is the detection of the presence of L. monocytogenes in raw milk in the region of Batna using the real-time polymerase chain reaction (real-time PCR) technique, in order to assess the riskrun by the consumer of raw milk in the study area. 65 milk samples were investigated for the detection of L. monocytogenes. The detection of the hlyA gene in all samples was done by real-time PCR assay by comparative cycle threshold method. The results obtained were negative for all the samples analyzed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Also, individual studies from Southern Africa have reported Lm prevalence in milk as 1.00% in raw milk in Botswana 30 , 8.00% in pasteurized milk and 26.92% in raw milk in South Africa 1 . In the Northern Africa subregion, Lm prevalence from individual studies in milk ranged from 0.00 to 2.61% in raw and pasteurized milk in Algeria 31 – 34 , 0.0% in pasteurized milk (Ahmed et al 2022), 0.0–5.63% in powdered milk 6 , 35 , and 0.00–34.00% in raw milk 8 , 11 , 36 – 51 ; in Egypt. Previous individual studies on Lm contamination of milk in the Eastern African reported 0.00% 52 and 20.00% 53 in pasteurized milk, 2.34–22.00% 7 , 52 , 54 57 in raw milks in Ethiopia; 21.43% 58 in raw milk, 0.00% in boiled milk 59 , 0.00% in fermented milk 59 , 60 , and 0.00% 59 in pasteurized milk in Kenya; 0.00% 59 and 0.42% 61 in raw milk in Rwanda and Sudan respectively, 0.00% in fermented, pasteurized, and raw milks in Tanzania 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, individual studies from Southern Africa have reported Lm prevalence in milk as 1.00% in raw milk in Botswana 30 , 8.00% in pasteurized milk and 26.92% in raw milk in South Africa 1 . In the Northern Africa subregion, Lm prevalence from individual studies in milk ranged from 0.00 to 2.61% in raw and pasteurized milk in Algeria 31 – 34 , 0.0% in pasteurized milk (Ahmed et al 2022), 0.0–5.63% in powdered milk 6 , 35 , and 0.00–34.00% in raw milk 8 , 11 , 36 – 51 ; in Egypt. Previous individual studies on Lm contamination of milk in the Eastern African reported 0.00% 52 and 20.00% 53 in pasteurized milk, 2.34–22.00% 7 , 52 , 54 57 in raw milks in Ethiopia; 21.43% 58 in raw milk, 0.00% in boiled milk 59 , 0.00% in fermented milk 59 , 60 , and 0.00% 59 in pasteurized milk in Kenya; 0.00% 59 and 0.42% 61 in raw milk in Rwanda and Sudan respectively, 0.00% in fermented, pasteurized, and raw milks in Tanzania 62 .…”
Section: Discussionmentioning
confidence: 99%